Who Trusts in Gene-Edited Foods? Analysis of a Representative Survey Study Predicting Willingness to Eat- and Purposeful Avoidance of Gene Edited Foods in the United States - Cummings, Christopher; Peters, David J. (Frontiers in Food Science and Technology, 2022)
CRISPR-Cas, ZFN, and TALEN provide gene editing opportunities which may lead to new food and agricultural products with identifiable benefits for end-use consumers. Given the public perceptions and backlash faced by previous generations of genetically modified food products, there is a lot of speculation regarding how gene edited food products will come to be understood, and if they will be accepted or avoided by society. This study provides timely and reliable data which reports representative coordinated study of the United States public as to what factors influence their willingness to eat- or purposeful avoidance of gene-edited foods. This study fills this gap to identify influential factors which, in concert, help to explain not only if members of the public trust GEF and are willing to eat GEF foods or choose to avoid them, but why they hold the trust attitudes they do. From our analysis, we find that social values, institutional trust, and awareness are the most important factors in why Americans would choose to either eat or avoid gene edited foods. Surprisingly, the public’s attitudes about the tangible characteristics of food (such as safety, cost, taste, and appearance) had no bearing on GE food perceptions. This helps explains why the American public makes little distinction between willingness to eat processed or raw foods made with GE crops.